The interaction between stockpeople and buffaloes in parlor - Rodrigues, D. A. [UNESP]; Ramírez-Diaz, J. [UNESP]; Silva, A. A.; Rocha, L. M.; Tonhati, H. [UNESP] (My University, 2010)
Aiming evaluate the influence of the actions of stockpeople in buffaloes behavior in the parlor, 271 buffaloes were observed on day-control, in the morning, in mechanized milking, belonging to 3 properties in State of Sao Paulo, Brazil. We recorded the milking time (TO), the time spent in the parlor (TSO) for each dam, and yours movements in teat cup attachment moment (MOV: stop, pass or kick) and occurrence of urination or defecation in parlor. The actions of stockpeople were classified as positives and negative. The managements in properties were different concerning the frequencies of negative actions (Hitting: c2=11,94; df =2; p<0,01) and positive actions (Talk: c2=11,15; df =2; p<0,01; Naming: c2=7,51; df =2; p<0,05). The property I had a higher frequency of negative actions (30% the animals suffered assaults physical). In property III a higher frequency of positive actions (the stockpeople talked with 23% of the animals and were the only one to naming the buffaloes) were found. The property II had intermediate values of these actions. The property on which had greater proportion of negative actions were also higher frequencies of urination (c2=14,51; df=2; p<0,01) and defecation (c2=22,11; df=2; p<0,01), which showed to be dependent on the MOV (p <0.01), but there were no differences between the properties on this record (p = 0.08). When classfying activities in the parlor the frequency of animals reactive (kicking, urination and defecation) were also higher in the property I. Thus, we conclude that the treatment is carried out with negative and actions such as hitting the animal increases the reactivity of the buffaloes in the parlor.
Keywords: Buffaloes behavior; Milking; Welfare